Kajian Ekonomi Usahatani Padi Sawah (Oriza Sativa L.) Varietas Ciherang (Studi Kasus di Desa Reroroja Kecamatan Magepanda Kabupaten Sikka) - Refki Sanjaya (Fakultas Pertanian, Universitas Nusa Nipa, 2025)
A study was conducted in Reroroja Village, Magepanda District, Sikka Regency. The purpose of this study was to determine the planting pattern applied by rice farmers, to determine the cost structure, income and profits received by rice farmers, to determine the efficiency of rice farming in Reroroja Village, Magepanda District, Sikka Regency. The results of the study showed that the planting pattern applied by Ciherang variety rice farmers in Reroroja Village was a monoculture planting pattern for the first planting season and a planting pattern for the second planting season by means of crop rotation where planting two or more types of crops was done in rotation. After planting one harvest, then the next crop was planted on the same land. The average production of Ciherang rice in the first planting season was 2,366 kg and in the second planting season was 1,183 kg with a total of 3,549 kg for both planting seasons. The price of rice produced by farmers was Rp. 8,000 / kg, while in the second planting season the price of rice received by farmers was Rp. 10,000 / kg. In the first planting period, the average income was Rp. 18,924,000, and the second planting period was Rp. 11,830,000, so that the total income of the Ciherang variety of rice farmers during the two planting periods was Rp. 30,749,540. The average production cost was Rp. 3,343,912 for the first planting period and Rp. 3,343,912 for the second planting period, while the average total production cost for the two planting periods was Rp. 6,687,824. The average profit received by farmers for the first planting period was Rp. 15,584,088 and for the second planting period the average profit received was Rp. 8,486,088 with a total profit for the two planting periods of rice in Reroroja Village of Rp. 24,070,176.